Highlights of the INVC bridging activity project review and planning meeting; 29 – 30 June 2017 - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2017)
The Integrating Nutrition in Value Chains (INVC) Bridging Activity project was launched in June 2016 as a 2-year relay project between INVC 1 and its successor project, Agricultural Diversification for Incomes and Nutrition (ADIN). Funded by the USAID Malawi Country Mission, the 2016/2017 cropping season was the first one under the INVC BA project. Partners implemented activities aimed at providing continuity to a subset of smallholder farmer groups and EPAs that were supported under INVC 1. On 29 – 30 June 2017, project partners met in Lilongwe to review project implementation progress and discuss transition from the Bridging Activity to ADIN. This video provides highlights from this event.